Mechanical Characteristics and Stress Evolution of Cemented Paste Backfill: Effect of Curing Time, Solid Content, and Binder Content - Hou, Chen; Yang, Liujun; Li, Lei; Yan, Baoxu (Frontiers in Materials, 2022)
The clarification of the variation on the strength of the cemented paste backfill (CPB) under the coupling of multi-factor is the foundation of the CPB design of the mine. In this paper, the physical and mechanical properties of the CPB under the coupling effect of curing time, solid content and binder content were experimentally and theoretically investigated. The results show that: (1) The strength shows a parabolic growth trend with curing time, while the 3d can be regarded as the turning point of the trend. (2) The increase in binder content can effectively increase the later strength of CPB. (3) A sensitivity parameter considering the span of multi-factor was constructed, indicating that the curing time has the greatest impact on uniaxial compressive strength (UCS), and the variation in solid content has the least impact on it, which can be verified by the stress-strain curves. (4) Curing time and binder content can effectively change the stress evolution, which is reflected in reducing the strain corresponding to the peak stress, enhancing the characteristics of the peak stress and increasing stress drop. The results of this study aim to explain the essence of the influence of each factor on the mechanical behavior of CPB in the view of stress-strain evolution, which will help to better understanding the mechanical characteristics of CPB, quantify the sensitivity of the mechanical properties to various factors.